Epidemiologic synergy - the contribution of heterosexual HIV transmission to the spread of HIV among men who have sex with men (MSM) in South Africa - Mulongeni, Pancho (Institute of Infectious Disease and Molecular Medicine, 2017)
Background: Could heterosexual HIV transmission be a driver of HIV infections that occur in men who have sex with men (MSM)? Noting the disproportionately high HIV prevalence among MSM across a variety of settings, this subpopulation is often considered as sources of new infections, overlooking the possibility of HIV transmission from the heterosexual – general – population to MSM. Objective: To assess the relative contribution of heterosexual transmission of HIV for onwards transmission of HIV from one man to another. Method: An agent based model of heterosexual transmission of HIV in South Africa was extended to simulate the HIV epidemic among MSM from 1990 to 2012. The model included gay men (who only have sex with men), bisexual men (who have partners of both sexes) in addition to men who have sex with women. HIV prevalence and sexual behaviour data collected among MSM in South Africa served as calibration data. Results: The model estimated that 28.7% (IQR: 27.4-28.9%) of MSM were HIV positive in 2010. By simulating a counterfactual HIV epidemic in South Africa, where HIV only spreads via male-male sex, we observe a decline in HIV incidence occurring in MSM by 56% over the period of 1990-2010, relative to the historical reality of HIV spreading via heterosexual and male-male sex. Analogously, HIV prevalence among MSM in 2010 under the counterfactual scenario reached only 10.0% (IQR 2.8- 17.4%), substantially less than HIV prevalence estimates from samples of MSM in South Africa. Conclusion: Roughly half of the HIV infections among MSM in South Africa can be attributed to the high levels of HIV prevalence in the general population. Scale up of interventions to target high risk behaviours with male partners should dispel possible misconceptions of bisexually active or heterosexual MSM as lower risk partners, relative to those MSM in gay communities.